The business of war military enterprise and military revolution in early modern Europe - Parrot, David (Cambridge University Press, 2012)
This is a major new approach to the military revolution and the relationship between warfare and the power of the state in early modern Europe. The book reveals the extraordinary prevalence and capability of private networks of commanders, suppliers, merchants and financiers who managed the conduct of war on land and at sea, challenging the traditional assumption that reliance on mercenaries and the private sector results in corrupt and inefficient military force.